Influence of Visual Deprivation on Auditory Spectral Resolution, Temporal Resolution, and Speech Perception - Shim, Hyun Joon; Go, Geurim; Lee, Heirim; Choi, Sung Won; Won, Jong Ho (Frontiers in Neuroscience, 2019)
We evaluated whether blind subjects have advantages in auditory spectral resolution, temporal resolution, and speech perception in noise compared with sighted subjects. We also compared psychoacoustic performance between early blind (EB) subjects and late blind (LB) subjects. Nineteen EB subjects, 16 LB subjects, and 20 sighted individuals were enrolled. All subjects were right-handed with normal and symmetric hearing thresholds and without cognitive impairments. Three psychoacoustic measurements of the subjects’ right ears were performed via an inserted earphone to determine spectral-ripple discrimination (SRD), temporal modulation detection (TMD), and speech recognition threshold (SRT) in noisy conditions. Acoustic change complex (ACC) responses were recorded during passive listening to standard ripple-inverted ripple stimuli. EB subjects exhibited better SRD than did LB (p = 0.020) and sighted (p = 0.003) subjects. TMD was better in EB (p < 0.001) and LB (p = 0.007) subjects compared with sighted subjects. SRD was positively correlated with the duration of blindness (r = 0.386, p = 0.024). Acoustic change complex data for ripple noise change at the Cz and Fz electrodes showed trends toward significant correlations with the behavioral results. In conclusion, compared with sighted subjects, EB subjects showed advantages in terms of auditory spectral and temporal resolution, while LB subjects showed an advantage in temporal resolution exclusively. These findings suggest that it might take longer for auditory spectral resolution to functionally enhance following visual deprivation compared to temporal resolution. Alternatively, a critical period of very young age may be required for auditory spectral resolution to improve following visual deprivation.